Development of an office building sustainability assessment framework for Malaysia - Shari, Zalina; Soebarto, Veronica (Universiti Putra Malaysia Press, 2017)
This paper presents a study aimed at developing a building performance assessment framework relevant to emerging/developing countries that allows evaluations on whether, and to what extent, sustainability is addressed in office building developments. Instead of simply adopting an existing building performance assessment framework, a framework developed through original work involving various relevant stakeholders in Malaysian building industry is presented. The process adopted a mixed-methods approach, particularly using exploratory sequential design i.e. a qualitative followed by a quantitative phase. The goal of the qualitative phase was to discover essential performance criteria through 1) literature review; 2) in-depth interviews; and 3) focus groups discussion. The performance criteria identified from the qualitative phase were brought into the quantitative phase via a questionnaire survey for the purpose of assigning their weighting levels. The tentative assessment framework was then presented to local experts for validation, and finally the Validated Comprehensive Malaysian Office Assessment (MyOBSA) framework is proposed. The framework covers all aspects of sustainability, thus allowing sustainability to be assessed in all phases of building developments, from pre-design to operational stages. This study demonstrates that any emerging/developing country shall be able to develop its own building sustainability assessment framework by taking into account relevant priorities of that country.